2007
DOI: 10.1253/circj.71.1879
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Expression of Circulating T Cells and Plasma Osteopontin Levels are Increased in Relation to Severity of Heart Failure

Abstract: steopontin is an adhesion molecule that was first identified in bone tissue, 1 and it has been demonstrated that cardiomyocytes are an important source of osteopontin in left ventricular (LV) hypertrophy in both humans and rodents. 2 Interestingly, Singh et al showed that osteopontin is dramatically increased in the LV myocardium of a heart failure (HF) model in rats, after transition from LV hypertrophy to HF. 3 Furthermore, in a genetic animal model of dilated cardiomyopathy, 4 inflammatory cells express ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(18 reference statements)
1
25
1
Order By: Relevance
“…26 OPN may play a role in plaque instability, and high plasma levels of OPN may reflect plaque instability or may be involved in plaque destabilization. Although plasma OPN levels are reportedly high in patients with heart failure, 27 none of the present patients had heart failure. In our study, high plasma levels of OPN were found to be related to further cardiovascular events in patients undergoing PCI, which is consistent with the results of a recent study by Minoretti et al 28 who investigated plasma OPN levels in patients with stable CAD and reported that OPN levels are independent predictors for adverse cardiovascular events.…”
Section: Discussioncontrasting
confidence: 64%
“…26 OPN may play a role in plaque instability, and high plasma levels of OPN may reflect plaque instability or may be involved in plaque destabilization. Although plasma OPN levels are reportedly high in patients with heart failure, 27 none of the present patients had heart failure. In our study, high plasma levels of OPN were found to be related to further cardiovascular events in patients undergoing PCI, which is consistent with the results of a recent study by Minoretti et al 28 who investigated plasma OPN levels in patients with stable CAD and reported that OPN levels are independent predictors for adverse cardiovascular events.…”
Section: Discussioncontrasting
confidence: 64%
“…Coskun et al found higher OPN concentrations in patients with acute coronary syndrome compared to patients with stable angina (48). Soe-jima et al showed that OPN production in peripheral T cells is increased in relation to the severity of heart failure (49). OPN presumably plays an important role in the development of atherosclerosis (25,50), acting in two different ways.…”
Section: Discussionmentioning
confidence: 99%
“…6 Plasma levels of osteopontin (OPN), a phosphorylated acidic glycoprotein involved in extracellular matrix inflammatory modulation, were related to the severity of HF. 8 An experimental model showed OPN is abundantly produced by activated T cells and macrophages, and its levels are markedly increased in the failing LV myocardium, indicating a potential role of OPN in the inflammatory processes occurring in the heart of severely ill patients supported by MCS.…”
mentioning
confidence: 99%